Penyalahgunaan Koleksi di Perpustakaan Nasional Republik Indonesia - Imaman, Kevin Berlianto (UI Scholars Hub, 2018)
The focus of this research is to identify some kind of collection misappropriation and the effort that has been done by the National Library of Indonesia. The National Library of Indonesia is also one of the libraries that provides open access to users in using some of its collections, this freedom is also prone to acts of misuse of collections. Thus it is important for a library to review this as a preventive measure in preserving its collection. This research use qualitative approach with case study method. The result of this research shows that between misappropriation collection forms include theft of collection, mutilation, vandalism, and unauthorized borrowing. Therefore, the attempt that has been done by the National Library of Indonesia is to use technology tools such as CCTV and to put the suspect to the black list in overcoming problems. This research suggest for the National Library of Indonesia to make written policy about preventive measures, strict punishment, and to make persuasive guideline to be good to the collection, for example, posters and banners.